Emotion regulation, academic buoyancy, and academic adjustment of university students within a self-determination theory framework: A systematic review - Kritikou, Marina; Giovazolias, Theodoros (Frontiers in Psychology, 2022)
The transition from secondary to tertiary education seems to be a stressful period for many students, since they need to adjust to the new academic environment. This paper is a systematic review of 4.285 articles. The aim of this review was to investigate the factors in the university environment associated with emotion regulation, academic buoyancy and academic adjustment of tertiary students within a self-determination theory framework in combination with the nascent third wave of Positive Psychology. 41 papers met the inclusion criteria, all of which were rated as either good or moderate quality. The bulk of the studies included in the systematic review reported individual factors, i.e. self-efficacy, intrinsic motivation, academic factors, i.e. intention to drop out, learning climate and family and social factors i.e. faculty, peer and parental autonomy support. In accordance with the third wave of Positive Psychology that focuses on how interpersonal and ecological factors create nurturing environments and positive institutions, the systematic review highlighted the factors that institutes should consider in order to help students adjust better to the academic environment.